JUVENTUDE(S), ITINERÁRIOS FORMATIVOS E PROJETOS DE VIDA: entre reformas e textos/documentos curriculares do Ensino Médio brasileiro (1990 – 2018) - Luciano Rodrigues Duarte (2023)
The study is part of the Research Program developed in the Study and Research Group School Culture Observatory (OCE), which takes as sources and objects the curricular texts/documents produced for formal and non-formal education spaces. It analyzes curricular texts/documents proposed for the (re)structuring, modernization and innovation of the last stage of basic education, that is, high school, from 1990 to 2018, namely: National Curriculum Guidelines for High School (DCNEM, 1998; 2012; 2018); the National Curriculum Parameters for High School (PCNEM, 1999); the Law 13.415 of 2017, and the Common National Curriculum Base for High School (BNCCEM, 2018). The investigation focuses on curricular policies, founded on discourses and intentions regarding the formation of Brazilian youth, articulated to the proposition of formative itineraries and youth protagonism. The text includes interlocutions with the relational theory, under the Bourdieusian perspective and the critical theory of curriculum. The methodological orientation anchored in the praxeological knowledge, essentially associated with the lexicon of Bourdieusian concepts, i.e., field, habitus and capital, aimed at unveiling the naturalization of market/neoliberal discourses in the field of curriculum policies for high school. This form of knowledge recovers the active notion of young people/youth as products and producers of a curricular subfield, called "high school", distant from the accumulated experiences in the course of individual trajectories. The distance is projected on the hypothesis that the curriculum policies developed instrumentalize demarcations of control, reproduction and innovation, at the same time that they respond to the proposition of formative itineraries, as carriers of successful contents, amid the discourses projected in a game in which the youth are more singularized than pluralized. The discourses as thus taken as bearers of the disciplinary contents of the practices instituted in this subfield, reconverting the curricular habitus into the perspective of an education subjected to meritocracy, protagonism, and resilience. The results of the investigation indicate the condition of projects essentially managed by a variable hegemony, obeying a logic of employability, constructor of a globalizing identity, proper to the legitimization of economic development. Key-Words: Curricular Texts/Documents; High School; Formative Itineraries; Youth Protagonism; Bourdieu.